1999
DOI: 10.1128/aem.65.5.1966-1972.1999
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of Escherichia coli O157:H7 in Food and Water by Immunomagnetic Separation and Solid-Phase Laser Cytometry

Abstract: Rapid, direct methods are needed to assess active bacterial populations in water and foods. Our objective was to determine the efficiency of bacterial detection by immunomagnetic separation (IMS) and the compatibility of IMS with cyanoditolyl tetrazolium chloride (CTC) incubation to determine respiratory activity, using the pathogenEscherichia coli O157:H7. Counterstaining with a specific fluorescein-conjugated anti-O157 antibody (FAb) following CTC incubation was used to allow confirmation and visualization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…5,6 For example, the magnetic property of Fe 3 O 4 and catalytic activity property of TiO 2 were widely well known and useful, and the inorganic particles could be coated on the polymer surface or be encapsulated in the interior of polymer matrix. Among variety of composite particles, magnetic polymer particles have been investigated enormously because of their diversified applications in cell separation, 7 food analysis, 8 and targeting drug delivery. 9,10 For magnetic polymer particles, a variety of encapsulation techniques have been developed including conventional emulsion polymerization, [11][12][13][14] precipitation polymerization, 15 suspension polymerization, 16 seeded polymerization, 17,18 soapless emulsion polymerization, 19,20 miniemulsion polymerization, [21][22][23] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 For example, the magnetic property of Fe 3 O 4 and catalytic activity property of TiO 2 were widely well known and useful, and the inorganic particles could be coated on the polymer surface or be encapsulated in the interior of polymer matrix. Among variety of composite particles, magnetic polymer particles have been investigated enormously because of their diversified applications in cell separation, 7 food analysis, 8 and targeting drug delivery. 9,10 For magnetic polymer particles, a variety of encapsulation techniques have been developed including conventional emulsion polymerization, [11][12][13][14] precipitation polymerization, 15 suspension polymerization, 16 seeded polymerization, 17,18 soapless emulsion polymerization, 19,20 miniemulsion polymerization, [21][22][23] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…). The enumeration of stained fluorescent cells with SPC such as the Scan RDI instrument offers an ultra-sensitive quantification of targeted cells for the detection of rare cells in the water volume analysed (generally 100 ml), such as E. coli or more generally, as pathogens (Pyle et al 1999;Pougnard et al 2002;Cools et al 2005;West et al 2006;Aurell et al 2004). Our results showed that DVC-FISH performed with either single or two monolabelled probes is not efficient to allow cell detection by SPC.…”
mentioning
confidence: 85%
“…11,[15][16][17] Hence, these gels can be expected to act as intelligent materials used in many fields, such as controlled or targeted drug release, 16,18,19 extraction, 20,21 and enzyme activity control. 22 Besides the intelligent polymeric networks, more and more attention has been drawn to the preparation of different kinds of magnetic polymeric composites in the past decades because of the applications of magnetism to various fields, such as cell separation, 23 protein purification, 24 targeted drug delivery, 25 environmental and food analyses, 26 organic and biochemical syntheses, 27 and industrial water treatment. 28 Endowed with unique magnetic properties that turn on upon the application of a strong magnetic field and turn off upon the removal of the field, superparamagnetic nanoparticles attract great interest in the form of polymeric composites.…”
Section: Introductionmentioning
confidence: 99%